Therapeutic Management of Anovulatory Follicle using CIDR Based protocol in a Repeat Breeder Heifer - Chandel, Anshul; Singh, Madhumeet (The Indian Journal of Animal Reproduction, 2022)
A Controlled internal drug releasing device (CIDR)- Prostaglandin F2α (PGF2α) based estrus synchronization protocol and post-insemination CIDR application led to successful conception and parturition in a repeat breeder anovulatory heifer.
Keywords: Repeat breeding; CIDR; Anovulation; PGF2α